Flavour enhancers/food seasoning from seaweeds and a method for producing and uses thereof - Mohamed, Suhaila; Matanjun, Patricia; Mohamed Mustapha, Noordin; Syed Muhammad, Sharifah Kharidah (2007)
A method for preparing a seaweeds based flavour enhancer/ seasoning with cardiovascular health promoting, degenerative disease preventing and organ protective properties comprises the steps of pre-treating seaweeds; pulverization or extracting the pre-treated seaweeds using solvent; with or without the addition of polyphenol rich plants/extracts and other food additives.